Polishing pad and manufacturing method of polishing pad
By adopting a sublayer with high stress relaxation rate and high tan δ in the polishing pad, the problem of incomplete edge-profile abnormal improvement in the prior art is solved, and better polishing performance and edge-profile control are achieved.
Patent Information
- Application Number
- JP2023169431
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
The existing polishing pads may have poor polishing performance when improving edge-profile abnormalities and fail to effectively improve the edge-profile abnormalities of ‘flip shape’.
A polishing pad with a specific sublayer that showed a stress relaxation rate of 20% or higher in stress relaxation tests and maintained tan δ of 0.12 or higher in dynamic viscoelastic measurements. The sub-layer contains bubbles in the shape of a crack and has a wet film or resin adhesion amount of 0.125 g/cm².
By using this sub-layer, the polishing pad can effectively improve the ‘spring shape’ edge-profile abnormality, and thanks to its excellent pressure responsiveness, it is easy to control the edge-profile, improving polishing performance.
Smart Images

Figure 2025059378000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing pad. In particular, the present invention relates to a polishing pad that can be suitably used for polishing optical materials, semiconductor wafers, semiconductor devices, substrates for hard disks, etc. In particular, the present invention is suitably used for polishing devices in which an oxide layer, a metal layer, etc. are formed on a semiconductor wafer. [Background technology]
[0002] Polishing of semiconductor wafers and the like is usually performed using a technique known as CMP, in which a polishing pad and the wafer are slid relative to each other under pressure while a slurry (polishing liquid) is supplied between them to flatten the wafer surface through a combined chemical and mechanical polishing action.
[0003] The CMP method will be described with reference to FIG. 1. As shown in FIG. 1, a polishing apparatus 1 for carrying out the CMP method is provided with a polishing pad 3, which is in contact with a polished object 8 held by a holding platen 16 and a retainer ring (not shown in FIG. 1) for holding the polished object 8 so as not to shift, and includes a polishing layer 4, which is a layer for polishing, and a base layer 6 for supporting the polishing layer 4. The polishing pad 3 is rotated while the polished object 8 is pressed against it, and polishes the polished object 8. At that time, a slurry 9 is supplied between the polishing pad 3 and the polished object 8. The slurry 9 is a mixture (dispersion liquid) of water, various chemical components, and hard fine abrasive grains, and the chemical components and abrasive grains in the slurry are flowed and move relative to the polished object 8, thereby increasing the polishing effect. The slurry 9 is supplied to the polishing surface through grooves or holes and discharged.
[0004] Incidentally, the polishing pad 3 has conventionally been one that uses polyurethane foam for the polishing layer 4, but this can cause profile abnormalities in the workpiece 8, particularly in the edge portion, which is the periphery of the workpiece 8. Abnormalities in the edge profile can occur in oxide film polishing, where the edge of the workpiece is polished more than the center, resulting in over-polishing known as "edge droop," or a polishing defect known as "rebound," where unevenness appears on the peripheral area slightly inside the edge. In metal film polishing such as Cu film (damascene structure), the edge of the workpiece is not polished as much as the center, resulting in a "spring shape."
[0005] Patent Document 1 discloses a polishing pad that prevents "edge sagging" while suppressing the occurrence of polishing scratches by controlling the hardness of the polishing layer within a certain range by making the structure of the bubbles in the foam specific. Patent Document 2 discloses a polishing pad that does not have the problem of "edge sagging" by setting the hardness and tear strength of the polishing layer within a specified range. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-714 A [Patent Document 2] JP 2016-190313 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the polishing pads described in Patent Documents 1 and 2 above require specific physical properties and bubble structures of the polishing layer, and even if the "edge droop" is improved, other polishing performance may be inferior. In addition, although the "edge droop" is improved, there is no mention of improving the "flare shape", which is another edge profile abnormality.
[0008] The present invention has been made in consideration of the above problems, and aims to provide a polishing pad that enables improvement of the flange shape without significantly changing the physical properties and bubble structure of the polishing layer. [Means for solving the problem]
[0009] In view of the above problems, the present inventors conducted extensive research and discovered that the "flared shape" can be improved by using a specific base material layer, thereby completing the present invention. That is, the present invention includes the following. [1] A polishing pad comprising a polishing layer having a polishing surface for polishing an object to be polished, and a base layer disposed on the opposite side of the polishing surface of the polishing layer, The base layer has a stress relaxation rate of 20% or more after 200 seconds in a stress relaxation test using MAG; The polishing pad, wherein the base layer has a tan δ of always 0.12 or more at 20 to 100° C. as measured by dynamic viscoelasticity measurement in a compression mode. [2] The base layer contains teardrop-shaped bubbles and has a wet-formed film or resin coating weight of 0.125 g / cm 3 The polishing pad according to [1], which is a resin-impregnated nonwoven fabric having the following structure: [3] The polishing pad according to [1], which is a polishing pad for polishing metal. [4] A polishing method for polishing a workpiece having a metal surface, comprising the steps of: Providing an object to be polished having a metal surface; and bringing the polishing surface of the polishing pad according to claim 1 into contact with the metal surface to polish the metal surface. Effect of the Invention
[0010] The polishing pad of the present invention uses a low-resilience material for the base layer, which has a stress relaxation rate of 20% or more after 200 seconds in a MAG stress relaxation test and a tan δ of always 0.12 or more at 20 to 100°C in a dynamic viscoelasticity measurement in compression mode, thereby suppressing edge profile abnormalities (especially the shape of a metal film).In addition, the excellent pressure responsiveness makes it easy to control the edge profile. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a perspective view of a polishing apparatus 1. As shown in FIG. [Diagram 2]FIG. 2(a) is a perspective view and (b) is a cross-sectional view of a polishing pad 3 of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of the polishing object 8 in a fin-shaped state. [Figure 4] FIG. 4 is a film thickness profile of a polishing pad according to the prior art, showing a method for measuring the film thickness difference. [Diagram 5] FIG. 5 shows a film thickness profile and a removal rate profile at the edge of an object polished by a polishing pad of the prior art along a straight line passing through the center of the object. [Figure 6] 6(a) and 6(b) show the results of repeated compression tests of substrates A and B using MAG. [Figure 7] FIG. 7 shows the results of stress change (stress relaxation rate) in successive compression / recovery tests. [Figure 8] FIG. 8 shows the results of dynamic viscoelastic testing in compression mode. [Figure 9] FIG. 9 shows the profile of the thickness of the Cu film at the edge of the workpiece when polishing was performed with varying polishing pressure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, a mode for carrying out the invention will be described, however, the present invention is not limited to the mode for carrying out the invention.
[0013] <<Polishing pad>> The structure of the polishing pad 3 will be described with reference to Fig. 2. As shown in Fig. 2, the polishing pad 3 includes a polishing layer 4 and a base layer 6. The shape of the polishing pad 3 is preferably disc-shaped, but is not particularly limited, and the size (diameter) can also be appropriately determined depending on the size of the polishing apparatus 1 equipped with the polishing pad 3, and can be, for example, about 10 cm to 2 m in diameter. In the polishing pad 3 of the present invention, the polishing layer 4 is preferably bonded to the base layer 6 via an adhesive layer 7, as shown in FIG. The polishing pad 3 is attached to a polishing platen 10 of the polishing apparatus 1 by a double-sided tape or the like arranged on a base layer 6. As shown in FIG. 1, the polishing pad 3 is rotated by the polishing apparatus 1 while pressing against an object 8 to be polished, and polishes the object 8 to be polished.
[0014] Here, we will explain the wavy shape, which is an abnormality in the edge profile. The wavy shape is a polishing defect phenomenon in which the edge portion of the polished object 8 is not polished as much as the central portion. Figure 3 is a cross-sectional view of the polished object 8, and it can be seen that the disk-shaped polished object 8 has an edge portion (end portion) 8a that is not polished as much as the central portion. This is the wavy shape. Note that in Figure 3, the wavy shape is depicted enlarged for ease of understanding. In this specification, the strength of the ripple shape is expressed by measuring the film thickness of the thin film when the polished object has a thin film such as Cu. Figure 4 shows the film thickness difference caused by the ripple shape, and is a profile of a polished object showing a typical ripple shape when a conventional polishing pad is used. As shown in Figure 4, the distance from the thickest film thickness at the end of the polished object to the thinnest film thickness is taken as the film thickness difference. When the workpiece does not have a thin film, the profile of the total thickness of the workpiece is measured, and the evaluation can be performed by measuring the distance from the thickest part at the end to the thinnest part in the same manner as in Fig. 5. In this specification, for convenience, the ripple shape is evaluated using the film thickness difference in the workpiece having a Cu thin film.
[0015] FIG. 5 shows the Cu film thickness profile (FIG. 5-1, FIG. 5-3, FIG. 5-5) in which the vertical axis is the thickness of the Cu film and the horizontal axis is the distance along a line passing through the center of the polished object (the center of the polished object is set to 0, and the part 140-150 mm from the center) for a polished object having a Cu film polished by a conventional polishing pad, and the polishing rate profile (FIG. 5-2, FIG. 5-4) in which the vertical axis is the polishing rate (RR) and the horizontal axis is the distance along a line passing through the center of the polished object (the center of the polished object is set to 0, and the part 140-150 mm from the center) for a polished object having a Cu film polished by a conventional polishing pad. As can be seen from the Cu film thickness profile before polishing in FIG. 5-1, the Cu film originally has a slightly jumping shape in which the film thickness at the edge part becomes suddenly thicker. In other words, the film thickness at the edge part is thicker than the other parts by about 1500 angstroms (hereinafter, the difference between the film thickness at the edge part and the film thickness at the other parts is referred to as the film thickness difference). Figure 5, 2 (top right) shows the polishing rate profile after the first polishing, where the polishing rate of the edge portion is about 1200 angstroms faster than the other portions. Figure 5, 3 (middle left) shows the thickness profile of the Cu film after the first polishing, where it can be seen that the film thickness difference has decreased to about 1000 angstroms. Figure 5, 4 (middle left) shows the polishing rate profile after polishing again (second time), where the polishing rate of the edge portion is 300 angstroms faster than that slightly inside the edge portion (147 mm part), but is about the same as that of the portion closer to the center (142 mm or less). Figure 5, 5 (bottom) shows the thickness profile of the Cu film after polishing twice, where the film thickness difference remains at 1000 angstroms, and the 1000 angstrom ridge shape still remains. That is, even when polishing is performed multiple times with a conventional polishing pad, there is no improvement in the film thickness difference of the resulting polished object, and the film thickness difference is not desirable. It should be noted that the "flared shape" can be problematic in semiconductor polishing (particularly the process of polishing metal films) when the difference in film thickness between the outermost edge (periphery) of the workpiece to be polished and other parts of the workpiece exceeds 350 angstroms. Therefore, in this specification, a flared shape where the difference in film thickness exceeds 350 angstroms is considered to be a flared shape that should be improved.
[0016] <Polishing layer> (composition) The polishing pad 3 includes a polishing layer 4 that is a layer for polishing an object to be polished 8. The material constituting the polishing layer 4 can be suitably selected from polyurethane resin, polyurea resin, and polyurethane-polyurea resin, and more preferably polyurethane resin. The size (diameter) of the polishing layer 4 is the same as that of the polishing pad 3 and can be about 10 cm to 2 mm in diameter, and the thickness of the polishing layer 4 can usually be about 1 to 5 mm. The polishing layer 4 is rotated together with the polishing platen 10 of the polishing device 1, and while a slurry 9 is poured onto it, the chemical components and abrasive grains contained in the slurry 9 are moved relative to the object 8 to be polished, thereby polishing the object 8 to be polished.
[0017] (grooving, embossing) It is preferable that the surface of the polishing layer 4 of the present invention facing the polished object 8 is grooved or embossed. The groove is not particularly limited, and may be either a slurry discharge groove communicating with the periphery of the polishing layer 4 or a slurry holding groove not communicating with the periphery of the polishing layer 4, or may have both a slurry discharge groove and a slurry holding groove. Examples of the slurry discharge groove include lattice grooves and radial grooves, and examples of the slurry holding groove include concentric grooves and perforations (through holes), and these may also be combined. In low-pressure polishing, the platen is rotated at high speed in order to reduce the pressing force against the workpiece 8 and to ensure the polishing rate. This may cause the so-called hydroplaning phenomenon, in which the slurry 9 exists in a layer between the polishing surface and the processing surface and interferes with the polishing process. This phenomenon can be suppressed by groove processing or embossing the polishing surface. It is also possible to promote the discharge of polishing waste and the movement of the polishing liquid. The cross-sectional shape may be U-shaped, V-shaped, or semicircular. There is no particular restriction on the pitch, width, and depth of the grooves. In addition, in order to improve the flatness of the polishing pad 3, a surface grinding process such as buffing may be performed on the polishing surface side or the surface opposite to the polishing surface of the polishing pad 3.
[0018] The polishing layer 4 is formed by casting a mixture of a urethane prepolymer obtained by reacting an isocyanate group-containing compound with a polyol compound, hollow microspheres, and a curing agent (chain extender), and slicing the cured foam. That is, the polishing layer 4 is dry molded.
[0019] The voids formed inside the polishing layer 4 are formed to have a substantially circular cross section by the hollow microspheres added to the dispersion liquid during dry molding. That is, in the polishing layer 4, a plurality of hollow microspheres are formed so as to overlap in the thickness direction, and can be formed substantially uniformly in two directions intersecting the thickness direction. Since the polishing layer 4 is formed by slicing a foam, some or all of the hollow microspheres may be open on the polishing surface. The average opening diameter of the openings formed on the polishing surface is adjusted to a range of 10 to 100 μm.
[0020] (Shore D hardness) The Shore D hardness of the polishing layer 4 of the present invention is not particularly limited, but is preferably 40 to 70. If the Shore D hardness is less than 40 degrees, it becomes difficult to flatten fine irregularities by low-pressure polishing. If it exceeds 70 degrees, the polishing particles are strongly rubbed against the polished object 8, and scratches may occur on the processed surface of the polished object 8. The lower limit of the Shore D hardness of the polishing layer 4 is preferably 40 or more, 42 or more, and 45 or more, in that order, and the upper limit is preferably 70 or less, 65 or less, and 60 or less, in that order.
[0021] (Poisson's ratio) The Poisson's ratio of the polishing layer 4 is not particularly limited. The Poisson's ratio of the polishing layer 4 is, for example, 0.20 to 0.50, and preferably 0.30 to 0.40. If the Poisson's ratio of the polishing layer 4 is smaller than 0.20, it may not show sufficient elasticity and the polishing rate may decrease. In addition, the upper limit of the Poisson's ratio is 0.5, and a material with a Poisson's ratio close to 0.5 is a special material such as a rubber material, which has strong water repellency and cannot hold polishing slurry, etc.
[0022] The polishing layer 4 preferably contains hollow microspheres 4A as necessary.
[0023] <Base material layer> (composition) The polishing pad 3 of the present invention has a base layer 6. Although the base layer may be called a cushion layer in the art, it will be called a base layer in this specification. The base layer 6 makes the contact of the polishing layer 4 with the workpiece 8 more uniform.
[0024] The material for the base layer 6 is not particularly limited as long as it has a stress relaxation rate of 20% or more after 200 seconds in a MAG stress relaxation test and a tan δ of always 0.12 or more at 20 to 100° C. in a compression mode dynamic viscoelasticity measurement, and examples of the material include resin-impregnated nonwoven fabric, flexible materials such as synthetic resins and rubber, foams with a cellular structure, etc. Examples of polymer materials and resins used for the base layer 6 include resins such as polyurethane, polyethylene, polybutadiene, and silicone, and rubbers such as natural rubber, nitrile rubber, and polyurethane rubber. When a foam having a cellular structure is used as the base layer 6, the cellular structure may be one in which voids are formed inside a nonwoven fabric or the like. In addition, a suede-like material having teardrop-shaped bubbles formed by a wet film-forming method or a sponge-like material having fine bubbles can be preferably used. From the viewpoint of stress relaxation rate and tan δ in dynamic viscoelasticity measurement in compression mode, a wet film-formed film or a resin-impregnated nonwoven fabric containing teardrop-shaped bubbles is preferred.
[0025] The wet-formed film containing teardrop-shaped bubbles is a resin film such as polyurethane having a foamed structure with teardrop-shaped bubbles formed therein, which is formed by preparing a resin solution in which a resin such as polyurethane resin is dissolved almost uniformly in an organic solvent, spreading the resin solution into a sheet, removing the organic solvent from the resin solution in a water-based coagulation liquid to coagulate and regenerate a resin body (polyurethane body) (wet-formed film), and washing and drying the resin body (polyurethane body) coagulated and regenerated in the coagulation and regeneration process.Preferably, the wet-formed film contains teardrop-shaped bubbles and exhibits rubber elasticity even when subjected to repeated compression tests using MAG.
[0026] The resin-impregnated nonwoven fabric is a nonwoven fabric impregnated with a resin, and is not particularly limited, but examples of the resin used for the resin-impregnated nonwoven fabric include polyurethane-based resins such as polyurethane and polyurethane polyurea, acrylic-based resins such as polyacrylate and polyacrylonitrile, vinyl-based resins such as polyvinyl chloride, polyvinyl acetate and polyvinylidene fluoride, polysulfone-based resins such as polysulfone and polyethersulfone, acylated cellulose-based resins such as acetylated cellulose and butyrylated cellulose, polyamide-based resins, polystyrene-based resins, etc. As the resin used for impregnation, a polyurethane resin is preferable from the viewpoint of exhibiting appropriate cushioning properties. The material of the nonwoven fabric is not limited as long as it is a common nonwoven fabric, and examples thereof include polyolefin-based, polyamide-based, and polyester-based materials, with polyester-based materials being preferred. The resin-impregnated nonwoven fabric can be produced by a conventional production method. For example, the production method of the nonwoven fabric used includes a method of entangling fibers such as a needle punch method. From the viewpoint of deformation amount during repeated compression tests using MAG and fluctuation of initial elastic modulus, resin-impregnated nonwoven fabrics with a small resin adhesion amount and large voids are preferred. The resin adhesion amount differs depending on the type, so it is not particularly limited, but generally, a resin adhesion amount of 0.125 g / cm 3 It is preferable that the concentration is 0.100 g / cm or less. 3 More preferably, the resin adhesion is 0.125 g / cm 3 If the resin adhesion amount exceeds this range, there is a risk that sufficient performance in improving the shape of the ribbon may not be exhibited. The resin adhesion amount is the weight of the resin contained per unit volume of the resin-impregnated nonwoven fabric.
[0027] (Stress relaxation rate) The base layer 6 has a stress relaxation rate of 20% or more after 200 seconds in a stress relaxation test using MAG. Here, stress relaxation refers to a phenomenon in which, when a material is kept in a certain deformed state (smaller than the breaking strain), a force (stress) acts to return it to its original shape, but this force decreases with time. The stress relaxation rate is the ratio of the stress that has decreased from the initial stress after a certain time has passed to the initial stress, and is calculated by (initial stress - stress after a certain time has passed) / initial stress x 100. If the stress relaxation rate is less than 20%, there is a risk that the material will not exhibit sufficient spring shape improvement performance. The stress relaxation rate is preferably 22% or more, and more preferably 25% or more. The stress relaxation test using MAG is a compression test performed using a MAG (Micro Autograph, Shimadzu Corporation, MST-1). In the MAG measurement, the sample was compressed in compression mode up to a stress of 300 g, the stroke was stopped there, and the change in stress while maintaining that stroke was measured.
[0028] (tan δ in compression mode dynamic viscoelasticity measurement) The base layer 6 has a tan δ of always 0.12 or more at 20 to 100° C. in a compression mode dynamic viscoelasticity test (DMA). A tan δ of always 0.12 or more at 20 to 100° C. means that when tan δ is measured over a range from 20 to 100° C., it never becomes less than 0.12 at any temperature from 20 to 100° C. Dynamic Mechanical Analysis (DMA) is a method for measuring the mechanical properties of a sample by applying a time-varying (oscillating) strain or stress to the sample and measuring the resulting stress or strain. Tan δ is the ratio (E'' / E') of E'' (loss modulus) to E' (storage modulus). If tan δ at 20 to 100°C is below 0.12, there is a risk that the spring shape improvement performance will not be sufficient. Tan δ at 20 to 100°C is preferably always 0.135 or more, and more preferably always 0.15 or more. Note that tan δ is the viscous effect caused by the viscous component, and a large value of this value means that the return from deformation is slow.
[0029] (Shore A hardness) The Shore A hardness of the base layer 6 is not particularly limited, but is preferably 20 to 70. The Shore A hardness of the base layer 6 is preferably 20 to 70, since it exhibits sufficient edge profile improving performance and also exhibits the cushioning properties required of the base layer.
[0030] (density) The density of the base layer 6 is not particularly limited, but is preferably 0.10 to 0.50 g / cm. 3 and more preferably 0.20 to 0.40 g / cm 3 If the density is within this range, cushioning properties can be ensured and the same polishing rate (removal speed, RR) as before can be achieved. The lower limits of the density are 0.10, 0.15, and 0.20 g / cm 3 The upper limit of density is 0.50 g / cm 3 Below 0.45g / cm 3 Below 0.40g / cm 3 The following order of preference is given: Note that the density referred to here does not refer to the density of the material itself, but to the density of the base layer 6 in a state in which air bubbles are included.
[0031] <Adhesive layer> The adhesive layer 7 is a layer for adhering the base layer 6 and the polishing layer 4, and is usually made of a double-sided tape or adhesive. The double-sided tape or adhesive may be any known double-sided tape or adhesive in the art (e.g., an adhesive sheet). The polishing pad 3 and the base layer 6 are bonded together by an adhesive layer 7. The adhesive layer 7 can be made of at least one adhesive selected from, for example, acrylic, epoxy, and urethane adhesives. For example, an acrylic adhesive is used, and the thickness can be set to 0.1 mm.
[0032] <<Polishing pad manufacturing method>> A method for producing the polishing pad 3 of the present invention will now be described.
[0033] <Abrasive layer material> The material of the polishing layer 4 is not particularly limited, but for example, the main component is preferably a polyurethane resin, a polyurea resin, or a polyurethane polyurea resin, and more preferably a polyurethane resin. Specific examples of the main component material include a material obtained by reacting a urethane bond-containing polyisocyanate compound with a curing agent.
[0034] Hereinafter, a method for producing the material of the polishing layer 4 will be described using an example in which a urethane bond-containing isocyanate compound, a polyol compound, and a curing agent are used.
[0035] Examples of a method for producing the polishing layer 4 using a urethane bond-containing polyisocyanate compound and a curing agent include a production method including: a material preparation step of preparing at least a urethane bond-containing polyisocyanate compound, an additive, and a curing agent; a mixing step of mixing at least the urethane bond-containing polyisocyanate compound, the additive, and the curing agent to obtain a mixed liquid for molding a molded body; and a curing step of molding the mixed liquid for molding a molded body into the polishing layer 4.
[0036] The material preparation process, the mixing process, and the molding process will be explained below.
[0037] <Material preparation process> To manufacture the polishing layer 4 of the present invention, a urethane bond-containing polyisocyanate compound and a curing agent are prepared as raw materials for a polyurethane resin molded body (cured resin). Here, the urethane bond-containing polyisocyanate is a urethane prepolymer for forming a polyurethane resin molded body. When the polishing layer 4 is to be a polyurea resin molded body or a polyurethane-polyurea resin molded body, a prepolymer appropriate for the purpose is used.
[0038] Each component will be described below.
[0039] (Polyisocyanate compound containing urethane bonds) The urethane bond-containing polyisocyanate compound (urethane prepolymer or simply prepolymer) is a compound obtained by reacting the following polyisocyanate compound with a polyol compound under commonly used conditions, and contains a urethane bond and an isocyanate group in the molecule. In addition, other components may be contained in the urethane bond-containing polyisocyanate compound within the range that does not impair the effects of the present invention.
[0040] The urethane bond-containing polyisocyanate compound may be a commercially available product, or may be a product synthesized by reacting a polyisocyanate compound with a polyol compound. The reaction is not particularly limited, and addition polymerization may be performed using a method and conditions known in the production of polyurethane resins. For example, the polyisocyanate compound may be added to a polyol compound heated to 40°C while stirring in a nitrogen atmosphere, and the temperature may be raised to 80°C after 30 minutes, and the reaction may be continued at 80°C for 60 minutes. The urethane bond-containing polyisocyanate preferably has an NCO equivalent of about 300 to 600. Therefore, when the urethane bond-containing polyisocyanate is a commercially available product, it is preferable that the NCO equivalent falls within the above range, and when it is produced by synthesis, it is preferable to adjust the NCO equivalent to the above range by using the following raw materials in an appropriate ratio.
[0041] (Polyisocyanate compounds) In this specification, the polyisocyanate compound means a compound having two or more isocyanate groups in the molecule. The polyisocyanate compound is not particularly limited as long as it has two or more isocyanate groups in the molecule. For example, diisocyanate compounds having two isocyanate groups in the molecule include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), naphthalene-1,4-diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), 4,4'-methylene-bis(cyclohexyl isocyanate) (hydrogenated MDI), 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3'-dimethyl- Examples of the polyisocyanate include diphenylmethane-4,4'-diisocyanate, xylylene-1,4-diisocyanate, 4,4'-diphenylpropane diisocyanate, trimethylene diisocyanate, hexamethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, p-phenylene diisothiocyanate, xylylene-1,4-diisothiocyanate, ethylidine diisothiocyanate, etc. These polyisocyanate compounds may be used alone or in combination of a plurality of polyisocyanate compounds.
[0042] The polyisocyanate compound preferably contains 2,4-TDI and / or 2,6-TDI.
[0043] (Polyol compounds as raw materials for prepolymers) In this specification, the polyol compound means a compound having two or more hydroxyl groups (OH) in the molecule. Examples of polyol compounds used in the synthesis of the urethane bond-containing polyisocyanate compound as a prepolymer include diol compounds, triol compounds, etc., such as ethylene glycol, diethylene glycol (DEG), butylene glycol, polyether polyol compounds, such as poly(oxytetramethylene) glycol (or polytetramethylene ether glycol) (PTMG), polyester diols, and combinations thereof. Among these, it is preferable to use polypropylene glycol, polyester diol, and diethylene glycol in combination. The polyester diol can be obtained, for example, by reacting a dicarboxylic acid compound with a diol compound. Examples of the dicarboxylic acid compound include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedioic acid, and dodecanedioic acid; unsaturated bond-containing dicarboxylic acids such as maleic anhydride, maleic acid, and fumaric acid; alicyclic polycarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as orthophthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, diphenic acid, and anhydrides thereof; and the like, which may be used alone or in combination. Examples of diol compounds used in the synthesis of polyester diols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol, and these can be used alone or in combination. Among the above, polyester diols of adipic acid and 1,4-butanediol, and polyester diols of adipic acid and diethylene glycol are preferred. The number average molecular weight (Mn) of the polyol compound is not particularly limited, and can be, for example, 500 to 2500. Here, the number average molecular weight can be measured by gel permeation chromatography (GPC). When measuring the number average molecular weight of the polyol compound from the polyurethane resin, it can also be estimated by GPC after decomposing each component by a conventional method such as amine decomposition. The above polyol compounds may be used alone or in combination of two or more.
[0044] (Additives) As described above, additives such as an oxidizing agent may be added to the material of the polishing layer 4 as necessary.
[0045] (hardening agent) In the method for producing the polishing layer 4 of the present invention, a curing agent (also called a chain extender) is mixed with a urethane bond-containing polyisocyanate compound, etc. in a mixing step. By adding the curing agent, in the subsequent molding step, the main chain terminal of the urethane bond-containing polyisocyanate compound bonds with the curing agent to form a polymer chain, which then hardens. Examples of the curing agent include ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis[3-(isopropylamino)-4- polyamine compounds such as 2,2-bis[3-(1-methylpropylamino)-4-hydroxyphenyl]propane, 2,2-bis[3-(1-methylpentylamino)-4-hydroxyphenyl]propane, 2,2-bis(3,5-diamino-4-hydroxyphenyl)propane, 2,6-diamino-4-methylphenol, trimethylethylene bis-4-aminobenzoate, and polytetramethylene oxide-di-p-aminobenzoate; ethylene glycol, Pyrene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3- Examples of polyhydric alcohol compounds include methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, glycerin, trimethylolpropane, trimethylolethane, trimethylolmethane, poly(oxytetramethylene) glycol, polyethylene glycol, and polypropylene glycol.The polyamine compound may have a hydroxyl group, and examples of such amine compounds include 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, etc. As the polyamine compound, a diamine compound is preferable, and it is more preferable to use, for example, 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylenebis-o-chloroaniline) (hereinafter abbreviated as MOCA). (Hollow microspheres) The polishing layer 4 may contain hollow microspheres 4A having an outer shell and hollow inside, if necessary. As described above, the material of the hollow microspheres 4A may be a commercially available product. Alternatively, a product obtained by synthesis using a conventional method may be used. The material of the outer shell of the hollow microspheres 4A is not particularly limited, but may be, for example, polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyethylene glycol, polyhydroxyether acrylate, maleic acid copolymer, polyethylene oxide, polyurethane, poly(meth)acrylonitrile, polyvinylidene chloride, polyvinyl chloride and organic silicone resin, and copolymers of two or more kinds of monomers constituting these resins. In addition, examples of commercially available hollow microspheres include, but are not limited to, Expancel series (trade name manufactured by Akzo Nobel), Matsumoto Microsphere (trade name manufactured by Matsumoto Yushi Co., Ltd.), etc. The gas contained in the hollow microspheres is not particularly limited, but may be, for example, a hydrocarbon, specifically, isobutane.
[0046] <Mixing process> In the mixing step, the urethane bond-containing polyisocyanate compound (urethane prepolymer) obtained in the preparation step, hollow microspheres, additives, and curing agent are fed into a mixer and stirred and mixed. The mixing step is carried out in a state where the components are heated to a temperature at which the fluidity of each component can be ensured.
[0047] <Forming process> In the molding process, the mixture for molding prepared in the mixing process is poured into a rod-shaped mold preheated to 30 to 100°C for primary curing, and then heated at about 100 to 150°C for about 10 minutes to 5 hours for secondary curing to form a cured polyurethane resin (polyurethane resin molded body). At this time, the urethane prepolymer and the curing agent react to form a polyurethane resin, and the mixture hardens.
[0048] In the molding process, the mixture is reacted in a mold as necessary to form a foam. At this time, the prepolymer is crosslinked and hardened by the reaction between the prepolymer and the hardener.
[0049] After obtaining the molded body, it is sliced into sheets to form a plurality of polishing layers 4. A general slicing machine can be used for slicing. During slicing, the lower layer portion of the polishing layer 4 is held, and the polishing layer 4 is sliced to a predetermined thickness starting from the upper layer portion. The slice thickness is set to a range of, for example, 1.3 to 2.5 mm.
[0050] The polishing surface of the resulting polishing layer 4 is subjected to groove processing as required.
[0051] Thereafter, a double-sided tape is attached to the surface of the polishing layer 4 opposite to the polishing surface of the polishing layer 4 obtained in this manner. There are no particular limitations on the double-sided tape, and any double-sided tape known in the art can be selected and used.
[0052] <Method of manufacturing base layer 6> As described above, examples of the material of the base layer 6 include impregnated nonwoven fabric impregnated with resin, flexible materials such as synthetic resin and rubber, and foams having a bubble structure. The base layer 6 can contain teardrop-shaped interconnected bubbles. Examples include impregnated nonwoven fabric materials in which resin fibers such as polyethylene and polyester (nonwoven fabrics, flexible films, etc.) are impregnated with a resin solution such as urethane; suede materials using resin materials such as urethane; and sponge materials using materials such as urethane; flexible synthetic resins and rubbers. Among these, the manufacturing methods of impregnated woven or nonwoven fabrics using polyurethane resins and suede materials using resin materials such as urethane will be described. The base layer 6 can be manufactured according to the manufacturing method described below, but commercially available products can also be used.
[0053] (For suede) In the process of forming the base material layer 6, the base material layer 6 is formed by a wet film formation. That is, the base material layer 6 is formed through the steps of a preparation step of preparing a resin solution in which polyurethane resin is dissolved almost uniformly in an organic solvent, a coagulation regeneration step of spreading the resin solution prepared in the preparation step into a sheet shape and removing the organic solvent from the resin solution in a water-based coagulation liquid to coagulate and regenerate a polyurethane body, and a washing and drying step of washing and drying the polyurethane body coagulated and regenerated in the coagulation regeneration step to form the base material layer 6, which will be described in the order of the steps below. Note that the resin of the suede material is not limited to polyurethane resin, but for convenience, the material will be described as polyurethane.
[0054] <Preparation process> In the preparation step, a polyurethane resin and, if necessary, an additive are dissolved in an organic solvent to prepare a resin solution. The resin solution is prepared by dissolving the polyurethane resin and the additives substantially uniformly in a water-miscible organic solvent capable of dissolving the polyurethane resin, removing aggregates by filtration, and then degassing under vacuum. As the organic solvent, N,N-dimethylformamide (hereinafter abbreviated as DMF), dimethylacetamide (hereinafter abbreviated as DMAc), etc. can be used. For example, DMF is used as the organic solvent. The polyurethane resin can be selected from polyester-based, polyether-based, polycarbonate-based, and other resins.
[0055] As additives to be added as required, pigments such as carbon black, hydrophilic activators that promote foaming, and hydrophobic activators that stabilize the solidification and regeneration of polyurethane resin can be used. By changing the type and amount of additives, the size and amount (number) of teardrop-shaped bubbles formed inside the base layer 6 can be controlled. To adjust tan δ, the material and organic solvent are appropriately selected, the mixing ratio of the resin and the organic solvent, the size and amount of the teardrop-shaped bubbles, and the thickness of the base layer 6 are appropriately set. For example, the polyurethane resin can be in the range of 45 to 62 parts and the DMF can be in the range of 8 to 32 parts per 100 parts of the resin solution.
[0056] <Coagulation regeneration process> In the coagulation regeneration process, the resin solution prepared in the preparation process is continuously applied (spread into a sheet) to the film-forming substrate, and the polyurethane resin is coagulated and regenerated into a sheet by immersing in a water-based coagulation liquid. The resin solution prepared in the preparation process is applied substantially uniformly to the strip-shaped film-forming substrate by a coating machine such as a knife coater at room temperature. At this time, the coating thickness (coating amount) of the resin solution is adjusted by adjusting the gap (clearance) between the coater and the film-forming substrate. In this example, the coating amount is adjusted so that the thickness of the substrate layer 6 is in the range of 0.5 to 2.0 mm. Flexible films, nonwoven fabrics, woven fabrics, etc. can be used as the film-forming substrate. When nonwoven fabrics or woven fabrics are used, in order to suppress the penetration of the resin solution into the film-forming substrate when it is applied, a pretreatment (sealing) is performed by immersing the nonwoven fabrics or woven fabrics in water or a DMF aqueous solution (a mixture of DMF and water) or the like. When a flexible film such as a PET film is used as the film-forming substrate, the pretreatment is not required because it does not have liquid permeability.
[0057] The film-forming substrate coated with the resin solution is immersed in an aqueous coagulating liquid mainly composed of water, which is a poor solvent for polyurethane resin. In the aqueous coagulating liquid, micropores constituting a skin layer are first formed on the surface of the coated resin solution to a thickness of about several μm. Then, as the replacement of DMF in the resin solution with the aqueous coagulating liquid progresses, the polyurethane body is coagulated and regenerated in a sheet shape on one side of the film-forming substrate. DMF is removed from the resin solution, and DMF is replaced with the aqueous coagulating liquid, forming a large number of teardrop-shaped bubbles in a three-dimensional mesh shape in the polyurethane body. At this time, since the PET film of the film-forming substrate does not allow water to penetrate, the solvent is removed on the surface side (skin layer side) of the resin solution, and teardrop-shaped bubbles with a larger pore size are formed on the film-forming substrate side than on the surface side. That is, inside the polyurethane body, a large number of bubbles with rounded and approximately triangular cross sections are formed in a substantially uniformly distributed state along the thickness direction of the polyurethane body.
[0058] <Cleaning and drying process> In the washing and drying process, the strip-shaped (long) polyurethane body that has been coagulated and regenerated in the coagulation and regeneration process is washed and then dried to form the base layer 6. That is, the polyurethane body is washed in a washing liquid such as water to remove the DMF remaining in the polyurethane body. After washing, the polyurethane body is dried in a cylinder dryer. The cylinder dryer is equipped with a cylinder having a heat source inside. The polyurethane body passes along the circumferential surface of the cylinder to dry, and the base layer 6 is formed.
[0059] (In the case of resin-impregnated nonwoven fabric) A nonwoven fabric made of fibers such as polyester is immersed in a resin solution such as urethane resin, and after immersion, the resin solution is squeezed out using a mangle roller that can apply pressure between a pair of rollers, so that the nonwoven fabric is substantially uniformly impregnated with the resin solution. The nonwoven fabric is then immersed in a coagulating liquid made of water at room temperature to coagulate and regenerate the impregnated resin, thereby obtaining a resin-impregnated nonwoven fabric. The resin-impregnated nonwoven fabric is then removed from the coagulating liquid, and further immersed in a cleaning liquid made of water to remove N,N-dimethylformamide (DMF) from the resin, and then dried. After drying, the surface skin layer is removed by buffing to form the base layer 6.
[0060] <Joining process> In the bonding step, the formed polishing layer 4 and base layer 6 are bonded (bonded) with an adhesive layer 7. For example, an acrylic adhesive is used for the adhesive layer 7, and the adhesive layer 7 is formed to a thickness of 0.1 mm. That is, the acrylic adhesive is applied to the surface of the polishing layer 4 opposite the polishing surface P with a substantially uniform thickness. The surface of the polishing layer 4 opposite the polishing surface P and the surface of the base layer 6 are pressed together via the applied adhesive, and the polishing layer 4 and base layer 6 are bonded with the adhesive layer 7. Then, after cutting into a desired shape such as a circle, an inspection is performed to confirm that there is no dirt or foreign matter attached, and the polishing pad 3 is completed.
[0061] <About the workpiece> The polishing pad described in the present specification can be used for any object to be polished, but it is effective for objects that are easily affected by the wavy shape. Objects that are easily affected by the wavy shape include objects having a metal film on the surface, and the polishing pad described in the present specification can be used to polish such metal films. The workpiece to be polished may be a wafer having a layer of SiO2, which is easy to etch, on which a metal film is formed. The metal of the metal film is not particularly limited, but is preferably a highly conductive metal such as gold, silver, or copper. EXAMPLES
[0062] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0063] In each of the examples and comparative examples, unless otherwise specified, "parts" means "parts by mass".
[0064] In addition, the NCO equivalent is a value indicating the molecular weight of the prepolymer (PP) per NCO group, which is calculated by (mass (parts) of polyisocyanate compound + mass (parts) of polyol compound) / [(number of functional groups per molecule of polyisocyanate compound × mass (parts) of polyisocyanate compound / molecular weight of polyisocyanate compound)-(number of functional groups per molecule of polyol compound × mass (parts) of polyol compound / molecular weight of polyol compound)].
[0065] (About the polishing layer) The same polishing layer A was used in all of the examples and comparative examples. The polishing layer A was manufactured as follows. 50 parts of an isocyanate-terminated urethane prepolymer having an NCO equivalent of 560, which is obtained by reacting 2,4-tolylene diisocyanate (TDI), polypropylene glycol (PPG) having a number average molecular weight of 1000, and diethylene glycol (DEG), and 50 parts of an isocyanate-terminated urethane prepolymer having an NCO equivalent of 600, which is obtained by reacting 2,4-tolylene diisocyanate (TDI), a polyester diol of adipic acid having a number average molecular weight of 2000 and 1,4-butanediol, and diethylene glycol (DEG), were mixed, and 3.5 parts of unexpanded hollow microspheres, the shell of which is made of an acrylonitrile-vinylidene chloride copolymer and in which isobutane gas is contained in the shell, were added and mixed to obtain a mixed liquid. The obtained mixed liquid was charged into a first liquid tank and kept warm. Next, 20.3 parts of MOCA was added as a curing agent to the second liquid tank separately from the first liquid, and kept warm in the second liquid tank. The liquids in the first liquid tank and the second liquid tank were each injected into a mixer equipped with two injection ports so that the R value, which represents the equivalent ratio of the amino group and hydroxyl group present in the curing agent to the terminal isocyanate group in the prepolymer, was 0.90. The two injected liquids were mixed and stirred while being injected into a mold of a preheated molding machine, and then the mold was clamped and heated at 80°C for 30 minutes to perform primary curing. After the primary cured molded product was demolded, it was secondary cured in an oven at 120°C for 4 hours to obtain a urethane molded product. The obtained urethane molded product was allowed to cool to 25°C, and then heated again in an oven at 120°C for 5 hours, and then sliced to a thickness of 1.3 mm to obtain a polishing layer.
[0066] (About the base layer) <Wet-coated film containing teardrop-shaped bubbles> Base layer A: Suede pad Polyester MDI (diphenylmethane diisocyanate) polyurethane resin was used as the polyurethane resin for the preparation. 25 parts of DMF solvent, 40 parts of DMF dispersion containing 20% carbon black as a pigment, and 2 parts of hydrophobic activator as a film formation stabilizer were added and mixed to 100 parts of 30% polyurethane resin solution to prepare a polyurethane resin solution. The obtained resin solution was applied to a PET substrate (thickness 0.188 mm) to a thickness of 0.7 mm, and the organic solvent was removed from the resin solution in a water-based coagulation liquid, and substrate layer A was prepared including the PET substrate. Substrate layer B: Suede pad Using the same material as substrate layer A, but changing the overall film thickness to 0.58 mm, and by changing the film formation conditions, a substrate layer B with a lower density and a higher hardness than substrate layer A was produced.
[0067] <About resin-impregnated nonwoven fabric> Base layer C: Resin-impregnated nonwoven pad Nonwoven fabric made of polyester fibers (density: 0.216 g / cm 3 ) was immersed in a urethane resin solution (manufactured by DIC Corporation, product name "C1367"). After immersion, the resin solution was squeezed out using a mangle roller capable of applying pressure between a pair of rollers, and the nonwoven fabric was approximately uniformly impregnated with the resin solution. Next, the nonwoven fabric was immersed in a coagulating liquid made of water at room temperature to coagulate and regenerate the impregnated resin, thereby obtaining a resin-impregnated nonwoven fabric. Thereafter, the resin-impregnated nonwoven fabric was taken out of the coagulating liquid and further immersed in a cleaning liquid made of water to remove N,N-dimethylformamide (DMF) in the resin, and then dried. After drying, the surface skin layer was removed by buffing treatment to prepare the base layer C. The resin adhesion amount of the base layer C was 0.09 g / cm 3 , the thickness was 1.30 mm. Base material layer D: A resin-coated nonwoven fabric pad ("SUBA400" manufactured by Nitta Haas Corporation) was obtained and used as the base material layer.
[0068] (Repeated compression test using MAG) A continuous compression / recovery test was carried out on the base material layers A and B using a MAG (Micro Autograph, Shimadzu Corporation, MST-1) to measure the amount of compressive deformation. The results are shown in Figure 6. It was found that the base layer B no longer exhibited rubber elasticity after repeated compression tests using MAG. The measurement conditions for MAG are as follows. ·Load: 50~300g / cm 2 ·Indenter: 20φ Sample: 40φ Compression speed: 0.3mm / min Number of cycles: 100
[0069] (Measurement of stress change (stress relaxation rate)) The base layers A to D were compressed to a stress of 300 g in compression mode using a MAG (Micro Autograph, Shimadzu Corporation, MST-1), the stroke was stopped there, and the stress change required to maintain that stroke was measured. From the measurement results, the stress relaxation rates after 200 seconds for the base layers A to D are shown in Table 1, and the stress changes for the base layers C and D are shown in Figure 7. The measurement results for the base layers C and D are shown in Table 1. It was found that the stress relaxation rate of the substrate layer C was greater than that of the substrate layer D.
[0070] (Dynamic viscoelasticity test) For the base layers A to D, a dynamic viscoelasticity test was carried out in compression mode using a TA Instruments RSA-G2 to measure the storage modulus E' and loss modulus E" and then tan δ was calculated. The measurement results for the base layers C and D are shown in FIG. 8, and Table 1 shows whether the dynamic viscoelasticity test results for the base layers A to D were 0.120 or more. The base layers A and C always had a tan δ of 0.120 or more at temperatures from 20 to 100°C. The measurement conditions for the dynamic viscoelasticity test are as follows. Frequency: 1Hz Sample: Length 1.5cm x Width 1.5cm x Thickness 0.125cm Test mode: Compression ·Measurement temperature: 40℃ Distortion range: 0.10% Initial load: 50g
[0071] (Shore A hardness measurement) The Shore A hardness of the substrate was determined from the indentation depth of the indenter pressed against the surface of the test piece via a spring in accordance with the Japanese Industrial Standards (JIS K 7311). The Shore A hardness of each substrate layer (simply referred to as "A hardness" in Table 1) is shown in Table 1.
[0072] [Table 1]
[0073] (Example 1 and Comparative Example 1) The polishing layer obtained above, base material layers A and B as suede-type base material layers, and base material layers A and B that had been subjected to repeated compression tests using MAG were joined together with 0.1 mm thick double-sided tape (having an adhesive layer made of acrylic resin on both sides of a PET base material), and the double-sided tape was attached to the side of the base material layer opposite the adhesive layer to produce the polishing pads of Example 1 and Comparative Example 1.
[0074] (Example 2 and Comparative Example 2) The polishing layer obtained above and base layers C and D as resin-impregnated base layers were joined with 0.1 mm thick double-sided tape (having an adhesive layer made of acrylic resin on both sides of a PET base material), and the double-sided tape was attached to the side of the base material layer opposite the adhesive layer to produce the polishing pads of Example 2 and Comparative Example 2.
[0075] (Polishing test) Polishing was carried out with the polishing pads of Examples 1 and 2 and Comparative Examples 1 and 2 under the polishing conditions below. During polishing, the thickness of the Cu film was measured at 121 points around the diameter. A profile of the thickness of the Cu film at the edge of the obtained polished object was obtained, and the distance from the most raised part of the edge to the most polished part was taken as the "film thickness difference" as shown in FIG. 4, and is shown in Table 2. It can be seen that the polishing pads of Examples 1 and 2 have a small wave shape at the edge. In addition, the Cu film thickness profile deteriorated in both substrates A and B that underwent repeated compression tests using MAG, but substrate B no longer exhibited rubber elasticity after the repeated compression tests, and the Cu film thickness profile deteriorated even more.
[0076] (polishing conditions) Grinding machine: F-REX300X (manufactured by Ebara Corporation) Disk: 34R (KINIK) Retainer ring: Retainer ring GXKD (manufactured by Ebara Corporation) Rotation speed: (table) 90 rpm, (polishing head) 81 rpm Grinding pressure: 1.6psi Polishing agent temperature: 20℃ Abrasive discharge rate: 200ml / min Abrasive: Cu slurry Polished object: Silicon wafer with Cu film (disc shape with a diameter of 300 mm) Polishing time: 60 seconds Pad break: 32N 20 minutes Conditioning: Ex-situ 32N2 scan
[0077] [Table 2]
[0078] (Regarding pressure responsiveness) Polishing was carried out under the above-mentioned polishing conditions using the above-mentioned polishing layer and polishing pads having various substrate layers (Figure 9). The vertical axis indicates the thickness of the Cu film, and the horizontal axis indicates the distance along a line passing through the center of the polished object (the center of the polished object is set to 0, and the part 140 to 150 mm from the center). Figure 9 shows the edge profile of the polished workpiece when the retainer ring pressure and AREA8 pressure during polishing are changed from -15% to +15% using a polishing pad that uses base layer C as the base layer. As can be seen from Figure 9, the polishing pad that uses base layer C has a profile that changes smoothly in response to pressure, which means that the pressure response at the edge is high and it is easy to control the edge profile of the polishing rate. A similar tendency was observed with base layer A. On the other hand, when polishing was performed with a polishing pad using substrate layer D as the substrate layer, no change in the thickness profile of the Cu film at the edge of the polished object due to changes in pressure during polishing was observed. [Industrial Applicability]
[0079] INDUSTRIAL APPLICABILITY The present invention provides a polishing pad that makes it possible to improve the profile abnormality of the edge portion, that is, the ridge shape, and thus contributes to the manufacture and sale of polishing pads and has industrial applicability.
[0080] 1 Polishing equipment 3 Polishing Pads 4 Polishing layer 6 Base material layer 7 Adhesive layer 8 Object to be polished 8a Wing Shape 9. Slurry 10 Polishing plate 11 Foundation 16 Holding Plate
Claims
1. A polishing pad comprising a polishing layer having a polishing surface for polishing an object to be polished, and a base layer disposed on the opposite side of the polishing surface of the polishing layer, the base layer has a stress relaxation rate of 20% or more after 200 seconds in a stress relaxation test using MAG; The polishing pad, wherein the base layer has a tan δ of always 0.12 or more at 20 to 100° C. as measured by dynamic viscoelasticity measurement in a compression mode.
2. The substrate layer contains teardrop-shaped bubbles, and the wet-formed film or resin coating amount is 0.125 g / cm 3 2. The polishing pad of claim 1, which is a resin-impregnated nonwoven fabric having a surface area of 100 nm or less.
3. 10. The polishing pad according to claim 1, which is a polishing pad for metal polishing.
4. A polishing method for polishing a workpiece having a metal surface, comprising the steps of: Providing an object to be polished having a metal surface; and a step of contacting the polishing surface of the polishing pad according to claim 1 with the metal surface to polish the metal surface.
Citation Information
Patent Citations
Polishing pad and method of polishing semiconductor wafer
JP2012000714A
Polishing pad
JP2016190313A